Synergistic Effect of Iron and Zinc Nanoparticles with Recommended Nitrogen Dose on Production and Grain Quality of Maize (Zea mays L.) Cultivars Under Drought Stress - Mohamed Abbas; Chunjie Tian; Mohamed K. I. Nagy; Maryam Sabry Al-Metwally; Xuewen Chen; Hashim M. Abdel-Lattif (Nitrogen)
Abiotic factors, such as drought, can significantly impact the vegetative growth and productivity of maize. To investigate the effects of the combined foliar application of zinc (Zn) and iron (Fe) nanoparticles with the recommended nitrogen dose (RND) on maize production and grain chemical composition under different water regimes, two field experiments were conducted in El-Ayyat city, Giza, Egypt, during the summer seasons of 2022 and 2023. This study utilized a split-split-plot experimental design with three replications. The main plots were designated to different water regimes (100, 80, 60, and 40% of estimated evapotranspiration), while the sub-plots were randomly distributed with Zn and Fe nanoparticle concentrations (0, 100, and 200 mg/L). The sub-sub-plots were randomly allocated to three maize cultivars (SC-P3062, SC-32D99, and SC-P3433). The results revealed that exposure to drought conditions resulted in a significant decline in the yield and yield-related attributes across all maize cultivars examined. Grain yield decreased by 10–50% under drought conditions. However, the foliar application of Zn and Fe nanoparticles was found to significantly improve grain yield, protein content, oil content, starch content, crude fiber, ash, and macro- and micronutrient concentrations in the maize cultivars under control and drought stress conditions. The foliar application of Zn and Fe nanoparticles at a concentration of 200 mg/L to the SC-P3433 maize cultivar led to the greatest grain yield per hectare, reaching 11,749 and 11,657 kg under the irrigation regimes with 100 and 80% total evapotranspiration, respectively. According to the assessment using the relative drought index, the SC-P3062 maize cultivar demonstrated tolerance (T) to water stress conditions. In conclusion, the foliar application of Zn and Fe nanoparticles (100–200 mg/L) effectively mitigated the negative effects of drought stress on maize plants. This approach can be recommended for farmers in arid and semi-arid regions to maintain and improve maize yield and grain quality under water-deficit conditions.